Aspectos biologicos de Canthon uturatus (Germar, 1813) e Canthidium (Canthidium) Megathopoides boucomont, 1928 (Coleoptera, Scarabaeidae) - Rodrigues, Sérgio R.; A.H. Flechtíviann., E. Carlos (Instituto de Ecología, A.C., 1997)
We studied food relocation habits and nidification behavior for the dung beetles Canthon lituratus (Germar) and Canthidium (Canthidium) megathopoides Boucomont. Observations were done in dung pads of Guzerá cattle present in open pasture in Selvíria, Mato Grosso do Sul State, Brazil. In Canthon Hturatus, a telecoprid species, males and females alone, as well as couples were observad foriniiig riunq balls. Intia-specific competition for the ball was observad. Once the ball was made, the C. Hturatus rnale clinibed on top of it and attracted a female, probably by releasing a pheromone. After the pair was established. botfi lolled the ball, after which mating occurred, on the soil surface. After mating, the ball was lolled for an additional distance, before being buried; males could follow female after mating or not The ball was then buried by the female; if the male was present, he placed himself on top of the ball while the female was burying ¡t. Diameter and distance in which the ball was rolled, besides time of mating, are provided. Em Canthidium (Canthidium) megathopoides, a paracoprid species, niales and females alone took portions of dung and pulled them to a oertain distance, aftei which the ga'ilery was büilt and provided with the dung fragmenta. No intra or inter-specilic competition for the balls was observed. The pair was probably formed after the gallery was dug. Gallery shape and dimensions, as well as distances the dung was removed, are given.